Clinical and Paraclinical Characteristics of Wilms Tumor in Children at the Vietnam National Children's Hospital - Ngoc Lan, Bui; Ngoc Linh, Nghiem (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 41 No 3DO - 10.25073/2588-1132/vnumps.4796, 2025)
Background: Wilms tumor is the most common renal malignancy in children. Its clinical manifestations are often nonspecific. Objective: To describe the clinical and paraclinical characteristics of Wilms tumor in pediatric patients at the Vietnam National Children’s Hospital. Methods: A cross-sectional descriptive study was conducted on 72 patients diagnosed from January 2018 to April 2024, and followed up until August 2024. Diagnosis was based on imaging and confirmed by histopathology. Results: The median age at diagnosis was 19 months. Female-to-male ratio was 1.12:1. Tumors were left-sided in 45.2%, right-sided in 42.4%, and bilateral in 10.9%. Abdominal mass was the most common presenting symptom (69.4%). Most patients were diagnosed at localized stages after pre-operative chemotherapy (I–III, 80.8%), and 8.3% had lung metastases. According to the SIOP histopathological risk classification, 82.6% were intermediate risk, 10.2% were low risk, and 7.2% were high risk. Conclusions: The majority of patients were diagnosed at an early stage. Clinical and histopathological features were consistent with previous international studies, emphasizing the importance of early imaging-based detection and appropriate risk stratification.